The role of stratosphere-troposphere coupling in the occurrence of extreme winter cold spells over northern Europe - Lorenzo Tomassini (Journal of Advances in Modeling Earth Systems, 2012)
Extreme cold spells over Northern Europe during winter are examined in order to address the question to what degree and in which ways stratospheric dynamics may influence the state of the troposphere. The study is based on 500 years of a pre-industrial control simulation with a comprehensive global climate model which well resolves the stratosphere, the MPI Earth System Model. Geopotential height anomalies leading to cold air outbreaks leave imprints throughout the atmosphere including the middle and lower stratosphere. A significant connection between tropospheric winter cold spells over Northern Europe and erosion of the stratospheric polar vortex is detected up to 30 hPa. In about 40 percent of the cases, the extreme cold spells are preceded by dynamical disturbances in the stratosphere. The strong warmings associated with the deceleration of the stratospheric jet cause the tropopause height to decrease over high latitudes. The compression of the tropospheric column below favors the development of high pressure anomalies and blocking signatures over polar regions. This in turn leads to the advection of cold air towards Northern Europe and the establishment of a negative annular mode pattern in the troposphere. Anomalies in the residual mean meridional circulation during the stratospheric weak vortex events contribute to the warming of the lower stratosphere, but are not key in the mechanism through which the stratosphere impacts the troposphere.